STUDY ON NOISE LEVEL IN THE SEBEŞ CITY (PANGEEA, 2025)
In this study I will present the results of the monitoring of the noise pollution obtained at the six monitoring points in the city of Sebeş. Over the three years, from 2015 to 2018, the noise level in Sebeş increased by an average of 4.7 dB. The most traffic routes in the city of Sebeş have been monitored to identify where the noise level is higher.
Keywords: noise pollution; noise; Sebeş